CD169 (Siglec-1) as a Robust Human Cell Biomarker of Toll-Like Receptor 9 Agonist Immunotherapy - Lende, Stine Sofie Frank; Pahus, Marie Høst; Monrad, Ida; Olesen, Rikke; Mahr, Anna R.; Vibholm, Line K.; Østergaard, Lars; Søgaard, Ole Schmeltz; Andersen, Anna Halling Folkmar; Denton, Paul W.; Tolstrup, Martin (Frontiers in Cellular and Infection Microbiology, 2022)
Immunotherapy is a promising therapeutic area in cancer and chronic viral infections. An important component of immunotherapy in these contexts is the activation of innate immunity. Here we investigate the potential for CD169 (Siglec 1) expression on monocytes to serve as a robust biomarker for activation of innate immunity and, particular, as a proxy for IFN- production. Specifically, we investigated the effects of Toll-like receptor 9 agonism with MGN1703 (lefitolimod) across experimental conditions ex vivo, in humanized mice, and in clinical trial participants. Ex vivo we observed that the percentage of classical monocytes expressing CD169 increased dramatically from 10% pre-stimulation to 97% 24 hrs after MGN1703 stimulation (p<0.0001). In humanized NOG mice, we observed prominent upregulation of the proportions of monocytes expressing CD169 after two doses of MGN1703 where 73% of classical monocytes were CD169 positive in bone marrow following MGN1703 treatment vs 19% in vehicle treated mice (p=0.0159). Finally, in a clinical trial in HIV-infected individuals receiving immunotherapy treatment with MGN1703, we observed a uniform upregulation of CD169 on monocytes after dosing with 97% of classical monocytes positive for CD169 (p=0.002). Hence, in this comprehensive evaluation ex vivo, in an animal model, and in a clinical trial, we find increases in the percentage of CD169 positive monocytes to be a reliable and robust biomarker of immune activation following TLR9 agonist treatment.